Hidden dichromatism in the Burrowing Parrot (Cyanoliseus patagonus) as revealed by spectrometric colour analysis - Masello, Juan F.; Lubjuhn, Thomas; Quillfeldt, Petra; Justus Liebig University Giessen (My University, 2009)
Bird colour perception differs fundamentally from that of humans. Birds have more cone types in the retina, including UV or violet cones, which enable them to perceive a wider spectral range. Thus, human colour perception can be deceiving when assessing functional aspects of bird plumage coloration, such as the intensity of sexual selection. In this study we measured reflectance spectra of different plumage regions of male and female Burrowing Parrot (Cyanoliseus patagonus) individuals. Although not obvious to human eyes, spectrometry revealed that adults are sexually dichromatic. Plumage regions with structure-based (blue) and structure-psittacofulvin pigment-based (green) coloration differed in achromatic brightness. In contrast, the psittacofulvin-based (red) region differed in spectral shape between the sexes. Thus, Burrowing Parrot is among the growing number of bird species which were formerly classed as sexually monochromatic based on human vision, but which are actually sexually dichromatic.
Keywords: Burrowing Parrot; Patagonia; Psittacofulvin-based coloration; Psittacofulvins; Sex differences; Sexual dichromatism; Structural coloration; ddc:570